Sleep paralysis in Italy: Frequency, hallucinatory experiences, and other features - Jalal, Baland (Transcult Psychiatry, 2020)
Previous research has found supernatural beliefs about sleep paralysis (SP) to be very prevalent in Italy, with over one third of SP sufferers believing that their SP might have been caused by a supernatural creature known locally as the Pandafeche. The current study further examined features of SP in Italy. All participants had experienced SP at least once in their lifetime. Participants were recruited from the general population (N =  67) in the region of Abruzzo. The Sleep Paralysis Experiences and Phenomenology Questionnaire (SP-EPQ) was orally administered to participants. As hypothesized, we found that Italians from the general population reported high lifetime rates of SP, prolonged duration of immobility during the event, and great fear of the experience (with as many as 42% of SP sufferers fearing that they could die from the experience), all of which were particularly elevated as compared to cultures where there are no such elaborate traditions of SP (e.g., Denmark). In addition, 78% of participants experienced some type of hallucination during their SP. The results we present here suggest that cultural beliefs about SP in Italy (e.g., as being caused by the Pandafeche, as reported elsewhere) potentially can profoundly shape certain aspects of the experience – a type of mind-body interaction.